KARAKTERISTIK PASIEN MALARIA DI PUSKESMAS SIABU KECAMATAN SIABU KABUPATEN MANDAILING NATAL TAHUN 2019 - MIFTAH KHOIRIAH; NURFADLY NURFADLY (JURNAL ILMIAH SIMANTEK, 2023)
Malaria is a disease caused by Plasmodium which is transmitted through female Anophelesmosquitoes as a vector. Malaria is still a public health problem in the world, including Indonesia, with high morbidity and mortality rates. The characteristics of malaria patients can be seen based on age, sex, occupation, level of education, and type of Plasmodium. To determine the characteristics of malaria patients at the Siabu Public Health Center, Siabu District, Mandailing Natal District in 2019. This study was a descriptive observational study with a cross sectional method. The population in this study was all patient data who were diagnosed with malaria at the Siabu Public Health Center, Siabu District, Mandailing Natal District in 2019. The sampling technique used the total sampling method. Retrieval of research data by taking all medical record data of malaria patients at the Siabu Public Health Center, Siabu District, Mandailing Natal District in 2019. The results of this study obtained 174 people diagnosed with malaria in 2019. The highest age group was aged <20 years, as many as 81 people ( 46.6%). Most of the sexes in malaria patients were male as many as 108 people (62.1%). Most jobs for malaria patients are farmers, as many as 68 people (39.1%). The highest level of education among malaria patients is SD, amounting to 102 people (58.6%). The most Plasmodium type in malaria patients was Plasmodium falciparum as much as 132 (75.8%). Malaria patients at the Siabu Public Health Center, Siabu District, Mandailing Natal District, in 2019, were mostly found at <20 years old, most of the sexes were men, the most occupations were farmers, the highest education level was elementary school, the most Plasmodium type was Plasmodium falcifarum.